Transformasi Metode Pengajaran Pendidikan Agama Islam Melalui Platform Digital: Tantangan dan Peluang - Uyun, Nadrotul; Husnunnimah, Husnunnimah; Anisa, Fitri; Inayah, Bidayatul; Ismail, Ismail (Arfannur: Journal of Islamic Education, 2025)
The rapidly evolving digital era necessitates a transformative imperative for Islamic Religious Education (PAI) to maintain its relevance and effectiveness for the current digital generation. While the integration of digital technology into PAI  holds great promise, it also presents various significant challenges. Crucial issues include the authenticity and validity of religious content disseminated in the digital sphere. Conversely, this digital transformation also unlocks immense, previously unimaginable opportunities. Technology enables global access to a wealth of diverse religious learning resources, transcending geographical and temporal boundaries. Furthermore, digitalization facilitates the development of interactive and participatory learning methods, which have proven to significantly boost student engagement and motivation. This literature review comprehensively analyzes and elaborates on the inherent challenges and opportunities in digitally-based Islamic religious instruction. The analysis indicates that for optimal adaptation, PAI absolutely requires the development of adaptive and dynamic strategies tailored to the characteristics of the digital era. These strategies must specifically emphasize the importance of providing adequate digital literacy for the entire educational ecosystem, while simultaneously ensuring the quality and authenticity of the content presented. Through this holistic approach, PAI can empower students with a religious understanding that is not only deep in substance but also relevant and contextual to the realities of modern life